On the effects of flow pulsation upon the performance of flow deflector for catalytic converter - Katsuya HIRATA (The Japan Society of Mechanical Engineers, 2017)
In automobile-exhaust systems, catalytic converters are the main components to produce substantial pressure drops, which induce engine-power loss and fuel-consumption rise. In addition to the need to reduce the pressure loss, the flow passing through the catalytic substrate should be as uniform as possible, which provides a uniform thermal distribution and high catalytic-conversion efficiency. The authors have reported that a flow deflector placed inside a catalytic-converter diffuser part can drastically reduce the pressure loss and improve the velocity-profile uniformity in comparison with the no-flow-deflector case (Hirata et al., 2006 & 2008). In those reports, the authors' concern is restricted only to steady flow, due to the authors' intention to reveal fundamental features precisely under a simple and general condition. On the other hand, actual exhaust flows often include various pulsative components. So, the authors investigate the effects of flow pulsation upon the flow-deflector performances such as the pressure-loss reduction and the flow-uniformity improvement. As a result, the authors reveal that the flow deflector can reduce the pressure loss and improve the velocity-profile uniformity in comparison with the no-flow-deflector case, even for pulsating flow as well as steady flow.